Improved Dielectric Properties of ZrO2-Doped Ba0.6Sr0.4TiO3 Thin Films Deposited by Reactive Magnetron Co-Sputtering - Cho, Kwang-Hwan; Kang, Chong-Yun; Yoon, Seok-Jin; Lee, YoungPak (KOREAN PHYSICAL SOC, 2008)
ZrO2-doped (Ba0.6Sr0.4)TiO3 (BST) thin films with different ZrO2 contents were deposited on (100) LaAlO3 substrates by reactive magnetron co-sputtering. The dielectric properties of the ZrO2-doped BST thin films were measured using a symmetrical stripline resonator with shorted ends ranging from 1 to 3 GHz. We demonstrated that doping with ZrO2 significantly improved the dielectric properties of the BST thin films. ZrO2 doping successfully reduced the dielectric loss tangent (tan delta) from 9.2 x 10(-3) (pure BST) to 2.9 x 10(-3) (ZrO2 doped BST). The results of this study showed that the BST films remained tunable in a range of 29 similar to 42.7 %, which is sufficient for tunable microwave device applications. Consequently, ZrO2 doping improved the figure of merit (K) for the films from K = 46.4 (pure BST) to K = 114.1 (ZrO2-doped BST).
Keywords: TUNABLE MICROWAVE APPLICATIONS; FERROELECTRIC MATERIALS; CERAMICS